An RORγt Oral Inhibitor Modulates IL-17 Responses in Peripheral Blood and Intestinal Mucosa of Crohn's Disease Patients - Bassolas-Molina, Helena; Raymond, Ernest; Labadia, Mark; Wahle, Joseph; Ferrer-Picón, Elena; Panzenbeck, Mark; Zheng, Jie; Harcken, Christian; Hughes, Robert; Turner, Michael; Smith, Dustin; Calderón-Gómez, Elisabeth; et al. (Frontiers in Immunology, 2018)
Background & Aims: Despite the negative results of blocking IL-17 in Crohn’s disease (CD) patients, selective modulation of Th17-dependent responses warrants further study. Inhibition of retinoic acid-related orphan receptor gamma (RORɣt), the master regulator of the Th17 signature, is currently being explored in inflammatory diseases. Our aim was to determine the effect of a novel oral RORɣt antagonist (BI119) in human CD and on an experimental model of intestinal inflammation. Methods: 51 CD patients and 11 healthy subjects were included. The effects of BI119 were tested on microbial-stimulated peripheral blood mononuclear cells (PBMCs), intestinal crypts and biopsies from CD patients. The ability of BI119 to prevent colitis in vivo was assessed in the CD4+CD45RBhigh T cell transfer model. Results: In bacterial antigen-stimulated PBMCs from CD patients, BI119 inhibits Th17-related genes and proteins, while upregulating Treg and preserving Th1 and Th2 signatures. Intestinal crypts cultured with supernatants from BI119-treated commensal-specific CD4+ T cells showed decreased expression of CXCL1, CXCL8 and CCL20. BI119 significantly reduced IL17 and IL26 transcription in colonic and ileal CD biopsies and did not affect IL22. BI119 has a more profound effect in ileal CD with additional significant downregulation of IL23R, CSF2, CXCL1, CXCL8, and S100A8, and upregulation of DEFA5. BI119 significantly prevented development of clinical, macroscopic and molecular markers of colitis in the T-cell transfer model. Conclusions: BI119 modulated CD-relevant Th17 signatures, including downregulation of IL23R while preserving mucosa-associated IL-22 responses, and abrogated experimental colitis. Our results provide support to the use of RORɣt antagonists as a novel therapy to CD treatment.